Abscisic Acid Mediates Drought-Enhanced Rhizosheath Formation in Tomato - Karanja, Joseph K.; Aslam, Mehtab Muhammad; Qian, Zhang; Yankey, Richard; Dodd, Ian C.; Weifeng, Xu (Frontiers in Plant Science, 2021)
The rhizosheath, commonly defined as soil adhering to the root surface, may confer drought tolerance in various crop species by enhancing access to water and nutrients under drying stress conditions. Since the role of phytohormones in establishing this trait remains largely unexplored, we investigated the role of ABA in rhizosheath formation of wild-type (WT) and ABA-deficient (notabilis, not) tomatoes. Both genotypes had similar rhizosheath weight, root length, and root ABA concentration in well-watered soil. Drying stress treatment decreased root length similarly in both genotypes, but substantially increased root ABA concentration and rhizosheath weight of WT plants, indicating an important role for ABA in rhizosheath formation. Neither genotype nor drying stress treatment affected root hair length, but drying stress treatment decreased root hair density of not. Under drying stress conditions, root hair length was positively correlated with rhizosheath weight in both genotypes, while root hair density was positively correlated with rhizosheath weight in well-watered not plants. Root transcriptome analysis revealed that drought stress increased the expression of ABA-responsive transcription factors, such as AP2-like ER TF, alongside other drought-regulatory genes associated with ABA (ABA 8′-hydroxylase and protein phosphatase 2C). Thus, root ABA status modulated the expression of specific gene expression pathways. Taken together, drought-induced rhizosheath enhancement was ABA-dependent, but independent of root hair length.